2017
DOI: 10.1002/hed.24728
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of promoter mutations in the TERT gene in oral cavity squamous cell carcinoma

Abstract: Our results show that mutations in the TERT promoter occur in patients with oral cavity SCC at a high frequency. This suggests that somatic TERT promoter mutations could play a vital role in the pathogenesis and progression of oral cavity SCC. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1131-1137, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 48 publications
3
39
4
Order By: Relevance
“…The recent discovery of two activating mutations within the core promoter of the TERT gene prompted the significant role of such genetic event in the development of many cancer types . In the current study, we investigated the presence of TERT promoter mutations in head and neck cancers and confirmed the high rate of hot spot nucleotide changes in oral SCC (60%), particularly in tongue tumours, and the rarity of such mutations in oropharyngeal SCC . The expression level of telomerase was comparable in HPV‐positive and HPV‐negative oropharyngeal SCC suggesting that the low expression of E6 and E7 oncoproteins, previously shown in these tumours, has little effect on the activation of TERT promoter …”
Section: Discussionsupporting
confidence: 61%
“…The recent discovery of two activating mutations within the core promoter of the TERT gene prompted the significant role of such genetic event in the development of many cancer types . In the current study, we investigated the presence of TERT promoter mutations in head and neck cancers and confirmed the high rate of hot spot nucleotide changes in oral SCC (60%), particularly in tongue tumours, and the rarity of such mutations in oropharyngeal SCC . The expression level of telomerase was comparable in HPV‐positive and HPV‐negative oropharyngeal SCC suggesting that the low expression of E6 and E7 oncoproteins, previously shown in these tumours, has little effect on the activation of TERT promoter …”
Section: Discussionsupporting
confidence: 61%
“…Chen et al screened for the DNA integration from a panel of onco-viruses including HPV, EBV, and BKV in different types of tumors, and they did detect the presence of insertion events, but integration breakpoints were located at other cancer-driving genes rather than the TERT locus [67]. However, another recent study showed that HPV DNA targeted the TERT locus for integration in cells and tumors derived from head and neck cancer [82], but more detailed and comprehensive analyses are required.…”
Section: Onco-viral Dna Insertionsmentioning
confidence: 99%
“…There is a partial overlap of the study populations of Eckel-Passow et al [ 71 ] and Pekmezci et al [ 63 ]; e includes grade I-IV hepatocellular carcinoma and clear cell ( n = 57) [ 107 ] and non-clear cell hepatocellular carcinoma, NOS ( n = 259) [ 107 ]; f includes widely invasive ( n = 126) [ 140 ] and minimaly invasive ( n = 44) [ 140 ] Hürthle cell carcinomas; g these cases were classified according to the AFIP criteria [ 220 ]. It does not seem to exist an overlap of the study populations of Landa et al [ 127 ] and Landa et al [ 133 ]; it may exist an overlap of the study populations of Kim et al [ 136 ] and Kim et al [ 137 ] and the study populations of Melo et al [ 125 ] and Melo et al [ 138 ]; h includes buccal ( n = 84) [ 158 ], gum ( n = 34) [ 158 ], lip ( n = 6) [ 158 ], tongue ( n = 63) [ 158 ], floor of mouth ( n = 22) [ 49 , 158 ], alveolar ridge ( n = 1) [ 49 ], mandibule ( n = 1) [ 49 ], hard palate ( n = 2) [ 49 ], supraglottis ( n = 4) [ 49 ], glottis ( n = 1) [ 49 ], tonsil ( n = 18) [ 49 ], larynx ( n = 2) [ 49 ], oropharynx/hypopharynx ( n = 1) [ 49 ] and hypopharynx ( n = 1) [ 49 ]; i includes pure ( n = 48) [ 49 ] and mixed ( n = 28) [ 180 ] desmoplastic melanoma; j includes cutaneous melanomas, NOS and spitzoid melanocytic neoplasms ( n = 56) [ 183 ], occult melanoma ( n = 34), chronically sun-damaged (CSD) ( n = 18) [ 179 ] and non-CSD melanomas ( n = 12) […”
Section: Figurementioning
confidence: 99%